Enhancing Critical Thinking and Affective Skills in Elementary School Students Through the Application of Salingtemas-Based LKPD - Intan Mutiasari; Nadia Aldyza; Zahriyanti Zahriyanti (Journal of Educational Sciences, 2026)
This research is motivated by the need for innovative science learning approaches to improve elementary students’ critical thinking skills and affective development in response to Indonesia’s low science literacy achievement. This research describes the implementation of SALINGTEMAS-based Student Worksheets in improving critical thinking skills and affective aspects of grade V students at SDN 3 Ulim on Ecosystem material. Using a qualitative approach with Nvivo15 software for data analysis, the study examines how LKPD integrates Science, Environment, Technology, and Society to create contextual and meaningful learning experiences. The implementation strategy emphasizes creative, innovative, and cooperative learning activities supported by comprehensive teaching materials including lesson plans and assessment instruments. Results demonstrate positive impacts on students' critical thinking, particularly in observation, analysis, and reasoning skills. The LKPD successfully cultivates positive affective responses including active participation, creativity, willingness to experiment, and healthy competitive spirit. Despite challenges such as time constraints, limited teaching aids, and varying student abilities, SALINGTEMAS-based LKPD proves effective in enhancing Ecosystem learning quality and developing students' scientific character. This approach offers a valuable integrated learning model for elementary education.